The investigation of particle acceleration in colliding-wind massive binaries with SIMBOL-X - De Becker, M. (2008)
An increasing number of early-type (O and Wolf-Rayet) colliding wind binaries (CWBs) is known to accelerate particles up to relativistic energies. In this context, nonthermal emission processes such as inverse Compton (IC) scattering are expected to produce a high energy spectrum, in addition to the strong thermal emission from the shock-heated plasma. SIMBOL-X will be the ideal observatory to investigate the hard X-ray spectrum (above 10 keV) of these systems, i.e. where it is no longer dominated by the thermal emission. Such observations are strongly needed to constrain the models aimed at understanding the physics of particle acceleration in CWB. Such systems are important laboratories for investigating the underlying physics of particle acceleration at high Mach number shocks, and probe a different region of parameter space than studies of supernova remnants.